2023
DOI: 10.1038/s41598-023-36826-6
|View full text |Cite
|
Sign up to set email alerts
|

Defining an optimal control for RNAi experiments with adult Schistosoma mansoni

Max F. Moescheid,
Oliver Puckelwaldt,
Mandy Beutler
et al.

Abstract: In parasites such as Schistosoma mansoni, gene knockdown by RNA interference (RNAi) has become an indispensable tool for functional gene characterization. To distinguish target-specific RNAi effects versus off-target effects, controls are essential. To date, however, there is still no general agreement about suitable RNAi controls, which limits the comparability between studies. To address this point, we investigated three selected dsRNAs for their suitability as RNAi controls in experiments with adult S.manso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Since a high amount of dsRNA (30 µg/mL for Smgpcr20 and 15 µg/mL for Smnpp26 and Smnpp40 , respectively) was used for the triple KD approach, we performed another control experiment to exclude that treatment with this high amount of dsRNA may negatively influence our results. To this end, we made use of dsRNA of the ampR gene of Escherichia coli , which in a recent study was shown to be suitable as “irrelevant” control dsRNA in RNAi experiments with S. mansoni ( 46 ). Since in the mentioned study, 30 µg/mL dsRNA had been used, we repeated the experiment here with 60 µg/mL dsRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Since a high amount of dsRNA (30 µg/mL for Smgpcr20 and 15 µg/mL for Smnpp26 and Smnpp40 , respectively) was used for the triple KD approach, we performed another control experiment to exclude that treatment with this high amount of dsRNA may negatively influence our results. To this end, we made use of dsRNA of the ampR gene of Escherichia coli , which in a recent study was shown to be suitable as “irrelevant” control dsRNA in RNAi experiments with S. mansoni ( 46 ). Since in the mentioned study, 30 µg/mL dsRNA had been used, we repeated the experiment here with 60 µg/mL dsRNA.…”
Section: Resultsmentioning
confidence: 99%
“…For this, the external standard curve design was employed to estimate integrated-EGFP in gDNA of the schistosome eggs (n = 3) as described (26). The standard curve is based on linear regression (y = 3.3857x+35.093, R 2 = 0.9979) established by a logarithm (20)-transformed initial DNA input, the pJCR53.2-SmUbi-EGFP-SmUbi plasmid was used as the dependent and the Ct value from the qPCRs as the independent variation (not shown). We estimated the EGFP transgene copy number in GSH1 by converting the observed Ct values to the logarithmic copy numbers using the equations obtained from the standard curve.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, RNA interference (RNAi) has been proven as the most suitable method for functional gene characterization. However, RNAi efficiency varies, and it can lead to ectopic effects (17)(18)(19)(20). To study GOI, knock-out (KO) models are common for various model organisms, but not yet established for trematodes or other helminths.…”
mentioning
confidence: 99%
“…Firstly, we employed gfp dsRNA as the control. Previous research on S. mansoni has indicated that gfp can cause changes in the expression of related genes [ 51 ]. Therefore, it is important to carefully choose appropriate controls that have been used in S. japonicum .…”
Section: Discussionmentioning
confidence: 99%